Penegakan Hukum Terhadap Penyelenggaraan Izin Reklame Di Kota Surabaya - Widyawati Boediningsih; Mikha Wijaya (SAPIENTIA ET VIRTUS, 2015)
Companies need to develop new products with the right and to harmonize the various factors that influence well. One factor is the advertisement for the installation of billboards of a company can introduce as well as marketing their products to the public indirectly. This can increase a company's product sales results. But too many billboards were built in the city and also a lot going on violations in the field of licensing billboards resulting forcibly dismantled billboards by the government of Surabaya. The violations occurred because some things, such as billboards violate the location permits, built in the green belt, no license, have not paid taxes. This is just one example of the violation committed by the public or the applicant.